2019
DOI: 10.1002/mp.13842
|View full text |Cite
|
Sign up to set email alerts
|

Propagation‐based x‐ray phase‐contrast tomography of mastectomy samples using synchrotron radiation

Abstract: Purpose Propagation‐based phase‐contrast computed tomography (PB‐CT) is a method for three‐dimensional x‐ray imaging that utilizes refraction, as well as absorption, of x rays in the tissues to increase the signal‐to‐noise ratio (SNR) in the resultant images, in comparison with equivalent conventional absorption‐only x‐ray tomography (CT). Importantly, the higher SNR is achieved without sacrificing spatial resolution or increasing the radiation dose delivered to the imaged tissues. The present work has been ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…There are no established sCT techniques that achieve cellular resolution in large soft tissues such as human organs. Phase-contrast based sCT 12,14,15 , specifically propagation-based imaging 16 , can theoretically be applied to image large, soft tissues. However, the X-ray beam coherence and X-ray source brilliance necessary to resolve cellular detail whilst penetrating into samples larger than a few millimetres, was not available at any synchrotron facility worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…There are no established sCT techniques that achieve cellular resolution in large soft tissues such as human organs. Phase-contrast based sCT 12,14,15 , specifically propagation-based imaging 16 , can theoretically be applied to image large, soft tissues. However, the X-ray beam coherence and X-ray source brilliance necessary to resolve cellular detail whilst penetrating into samples larger than a few millimetres, was not available at any synchrotron facility worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Research at the imaging and medical beamline (IMBL) of Australian Synchrotron also focusses on the propagation-based phase-contrast approach for BCT with synchrotron radiation on mastectomy specimens [80][81][82][83][84]. In 2018, the first freshlynot formalin fixateddissected mastectomy sample was scanned at the Australian Synchrotron with an energy of 32 keV and a MGD of 4 mGy which is comparable to conventional mammography [84].…”
Section: Propagation-based Phase-contrast Imaging At the Elettra Syncmentioning
confidence: 99%
“…Their outstanding studies, including the comparison of physical image quality and visual, radiological assessment, proved a better performance compared to conventional absorption based BCT. Although Gureyev et al finally concluded that this approach can be used in a complementary way in addition to the existing image modalities [82], it is rather unlikely to scan women in vivo at large-scale synchrotron facilities and thus, this approach is still far away from daily clinical application. Nevertheless, these results remain very promising and might be applied to conventional X-ray sources with other phase-contrast approaches.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Synchrotron imaging has a growing interest in clinical radiography diagnostics/treatments, and recent advances have increased the sensitivity of detection and resulted in significant reductions in radiation dose. [100][101][102] In the future, this will have significant implications in both clinical and veterinary medicine, using either nonsynchrotron sources or compact X-ray sources.…”
Section: Synchrotron Imaging Of Cardiorespiratory Function: Improvingmentioning
confidence: 99%